Metastasis of breast cancer to the bone - Wolska, Joanna; Wolski, Dariusz; Stanisławek, Andrzej; Weber, Dorota; Irzmańska-Hudziak, Anna (Journal of Education, Health and Sport, 2019)
Spinal metastases are a complex but common manifestation of primary cancer. The most common use of spinal metastases is breast, lung and prostate cancer. Management of patients suffering from spinal metastases, which take into account the characteristics of cancer and various methods of treatment consisting of surgery, radiotherapy and chemotherapy. Metastatic spine cancer surgery is used with a low risk of complications because it results in significant relief of pain and long-term survival burdens. Pain relief, prevention of bone complications and maintenance of quality of life are included in the recommendations in metastatic bone disease. Knowledge related to the pathophysiology of painful metastases is changing quite quickly. However, for analyzing the pathophysiology of painful bone metastases may be the key to analgesic effects with minimal side effects.